Answer:
-7
Explanation:
To find y, follow these steps:
4y - 2 (1 - y) = -44
First, distribute the -2 into the parenthesis:
4y - 2 + 2y = -44
The reason the 2y is positive is due to the fact that negative and negative cancel each other out and form a positive.
Now, combine like terms:
6y - 2 = -44
To get y, you need to isolate it from the constants. In order to do so, do the inverse relationship for the constant -2. To do this, add 2 to -44:
6y = -42
Now, divide six on both sides. You divide because six is currently being multiplied with y. Keep in mind that the 42 is still negative!
y = -7
Hope this helps!